Repetitive, Safe, and Automatic: The Experience of Appearance‐Related Behaviours in Body Dysmorphic Disorder. (26th September 2016) - Oakes, Alissa; Collison, James; Milne‐Home, Jo
Abstract : Objective: Body dysmorphic disorder (BDD) entails a preoccupation with a perceived appearance defect, which causes distress and/or functional impairment. The individual must also perform repetitive behaviours in response to these concerns (e.g., mirror checking, excessive grooming). Prior research has focused primarily on preoccupation, and behaviours have rarely been examined. As such, there is limited insight regarding how these activities are perceived by the sufferer. This study therefore examined how individuals with BDD experience these behaviours. Method: Eight individuals diagnosed with BDD completed a 60‐min, semi‐structured interview. Inductive thematic analysis was employed to investigate semantic themes within the data. Results: Three themes emerged: "Routine and repetitive", "Safety through control, " and "Natural and automatic." These findings portray a complex experience of distressing activities that may also provide comfort and safety, in time coming to embodying what "normal" constitutes for the individual. Conclusions: The experience of BDD behaviour is complex. Camouflaging and using make‐up provided a sense of relief and/or reassurance, whereas other behaviours were reported as distressing and likely to promote further concerns. Ironically, participants were seemingly dissatisfied with these symptoms, while also drawing comfort and a sense of identify from them. This inconsistent pattern of reward and punishment supports existing conceptual models of BDD, and may explain why these symptoms are so difficult to manage and/or change (i.e., via negative reinforcement). It also suggests that different types or categories of behaviour may exist for BDD (e.g., checking vs fixing behaviours), reflecting different functions and/or underlying motivations among individuals.